Field test for measuring VO2peak in parkour : a pilot study - Vuoriainen, Mika (2019)
Introduction. Parkour has become a widely followed physical activity and there are plans by Federation Internationale de Gymnasticque for it to become an Olympic event. However, the physical demands of the activity have not been thoroughly examined. The purpose of this study was to examine the physical demands of parkour from the perspective of oxygen consumption in an obstacle course and to develop a field test to estimate oxygen consumption of parkour movement at different velocities. Movement on the obstacle course consisted of vaulting and running. Vaulting is a parkour specific way to move over obstacles. Methods. A total of 10 male parkour athletes (mean age 26.3 ± 4.2 years) volunteered for the study. The subjects completed a test to voluntary exhaustion on a specifically designed obstacle course and testing protocol, while their oxygen consumption was measured with a portable measuring device. The obstacle course was designed, so that it can be used as a field test and the design was adapted from 20m shuttle-run test. Validity of the designed testing protocol for cardiovascular fitness testing was assessed by achievement of VO2max criteria (plateau in oxygen consumption, RER > 1.1, maximal heart rate and lactate values > 8). Data, from individual subjects, was pooled to create a regression line for the estimation of oxygen consumption in vaulting. Results. Designed testing protocol met VO2max testing criteria. All subjects achieved RER >1.1, lactate > 8 and maximal heart rate. In addition, in 89% of measurements a VO2 plateau was observed. The mean test duration was 12 minutes and 12 seconds. Mean RER-values increased to a level above 1.0 at speed 7.0 km/h. Mean VO2peak was 44.0 ± 1.65 ml/kg/min and a regression line followed formula y = 4.15 + 3.73x. Conclusion. The achievement of VO2max criteria and suitable test duration indicates that the field test protocol is valid for assessing cardiovascular fitness. The linear increase in oxygen consumption with increasing velocity, suggests that the achieved final speed could be used to estimate oxygen consumption in parkour field test. The observation that oxygen consumption was high for any given speed, indicates that vaulting requires more oxygen than what is usually observed in running at similar speeds. The results also indicate a large demand for anaerobic energy production in vaulting, even at low speeds.